2019
DOI: 10.1073/pnas.1902035116
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nuclear architecture, mechanics, and nucleocytoplasmic shuttling of epigenetic factors by cell geometric constraints

Abstract: Cells sense mechanical signals from their microenvironment and transduce them to the nucleus to regulate gene expression programs. To elucidate the physical mechanisms involved in this regulation, we developed an active 3D chemomechanical model to describe the three-way feedback between the adhesions, the cytoskeleton, and the nucleus. The model shows local tensile stresses generated at the interface of the cell and the extracellular matrix regulate the properties of the nucleus, including nuclear morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
204
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(236 citation statements)
references
References 53 publications
15
204
0
Order By: Relevance
“…Mechanical strain and loading have also been shown to modulate chromatin remodeling enzymes like histone deacetylase (HDAC) and histone acetyltransferase (HAT) (51) and induce rapid chromatin condensation (51). Increasing contractility has been shown to regulate levels of HDACs, whereas available spreading area has been implicated in modulating HAT (54). Recently, it has been shown that stiff-primed stem cells continue to express an epigenetic modification factor HAT1 and suppress histone deacetylation enzymes (HDACs) even after they move to a soft matrix (33).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical strain and loading have also been shown to modulate chromatin remodeling enzymes like histone deacetylase (HDAC) and histone acetyltransferase (HAT) (51) and induce rapid chromatin condensation (51). Increasing contractility has been shown to regulate levels of HDACs, whereas available spreading area has been implicated in modulating HAT (54). Recently, it has been shown that stiff-primed stem cells continue to express an epigenetic modification factor HAT1 and suppress histone deacetylation enzymes (HDACs) even after they move to a soft matrix (33).…”
Section: The Modelmentioning
confidence: 99%
“…Recent experiments support this notion by showing upregulated HAT1 and downregulated HDACs when cells are primed sufficiently (33). Although it is known that nuclear shape, chromatin structure, and epigenetic state of the cell depend on matrix stiffness (25,28,29,54), it remains unclear how quickly these nuclear markers change when cells move to a new environment. Experiments could be also performed in which nuclei of differentially-primed cells are imaged through live-cell microscopy over time to verify that the nuclear structure and shape remain locked according to their past primed state.…”
Section: Proposed Studies To Test Key Assumptions and Predictionsmentioning
confidence: 99%
“…further understand how the two-way feedback between stress and signaling guides nuclear gene expression 47 , dynamic force generation 48 , and cancer invasion 13 . Importantly, in the current analysis we limit ourselves to the consideration of a single ion species and the associated channels and transporters, and therefore neglect the requirement of charge neutrality.…”
Section: Figure 5: A) Non-uniform Solid Growth Stress Drives Spatial mentioning
confidence: 99%
“…Clearly, our framework could be used to analyze such biological systems and provide mechanistic insight into their dependence on ion transport and differential cell swelling. Future advancements should also focus on detailing the interdependence between dynamic actomyosin contractility and cell osmolarity, building on our previous work to further understand how the two-way feedback between stress and signaling guides nuclear gene expression 47 , dynamic force generation 48 , and cancer invasion 13 . Importantly, in the current analysis we limit ourselves to the consideration of a single ion species and the associated channels and transporters, and therefore neglect the requirement of charge neutrality.…”
Section: Figure 5: A) Non-uniform Solid Growth Stress Drives Spatial mentioning
confidence: 99%
“…In the recent years, probing the mechanical properties of the heterochromatin and the euchromatin has gained significant interest because of the discovery of potential mechanisms that transduce mechanical forces into biological signals inside the cell nucleus -resulting into the emerging field of nuclear mechanobiology [9][10][11] . Mechanotransduction inside the nucleus is known to play critical roles in development, physiology, homeostasis and diseases 12,13 .…”
Section: Introductionmentioning
confidence: 99%